Olbia in the Hunnic Time. A Historical Perspective - Alfred Twardecki (Archaeologia Polona)
In this paper, the author presents the historical background of the period of functioning of the site of Olbia in the Gothic and Hunnic periods. He presents the most important studies on the Goths and Huns in recent decades, reconstructs the course of the Gothic wars (third to sixth centuries) and analyses selected sagas of Germanic mythology. On the basis of this and using the results of the recent archaeological excavations, he formulates the thesis that Olbia, functioning in the Gothic period from the 3rd/4th centuries to the beginning of the 5th century AD, could have been an important administrative centre of pagan Goths who actively fought against their Christianized brethren. He also hypothesizes that it can be identified with the land of Oium (Olbium) and with the Árheimar á Danparstoeðum, the capital of Reiðgotaland, mentioned in the oldest Germanic sagas.